Spain : Basel Core Principles for Effective Banking Supervision: Detailed Assessment of Compliance Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper assesses compliance of the Basel Core Principles for Effective Banking Supervision in Spain. Significant changes have occurred in Spain since the last Financial Sector Assessment Program (FSAP). The most serious has been the deterioration of the economy and the real estate sector. The dual legal framework governing Cajas poses the risk of potential conflicts in the exercise of supervisory and sanctioning authority. Other 2006 FSAP recommendations have been magnified with the perspective given by events from 2007 to 2011.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet